WHY IS SUSTAINABILITY ACCOUNTING IMPLEMENTATION CRITICAL FOR HIGHER EDUCATION INSTITUTIONS? THE THEORETICAL ARGUMENTS - Kurniawan, Putu Sukma; Adiputra, I Made Pradana; Astawa, I Gede Putu Banu; Pramiswari, Ni Luh Putu Ayu Lastri (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
The present study aims to provide theoretical arguments to demonstrate why the implementation of sustainability accounting is crucial in the context of higher education institutions. The absence of substantial implementation of sustainability accounting in higher education institutions in Indonesia is a matter that requires resolution. This study provides a novel perspective in the form of theoretical arguments that demonstrate the significant importance of the implementation of sustainability accounting for higher education institutions, particularly in Indonesia. The present study employs a theoretical argumentation approach, drawing upon the insights of writers and the findings of preceding research. Theoretical arguments have been developed to provide a new perspective on the implementation of sustainability accounting in higher education institutions in Indonesia. This study concludes that the implementation of sustainability accounting has crucial benefits for the development of higher education institutions in Indonesia. The implications of this study can be continued by supporting the implementation of sustainability accounting by developing implementation policies and guidelines.